Smartphone-assisted Colorimetric Detection of Hg (II) in an Organized Medium Applying Polyethylene Glycol Monododecyl Ether Stabilized Silver Nanoparticles - Khan, Sarzamin; Rehman, Sabeela; Khan, Nazish Huma; Khan, Waseeq; Ali, Jawad; Toloza, Carlos A. T.; Tahir; Alzahrani, Eman; Zaibi (Current Analytical Chemistry, 2025)
<span class=
Keywords: aqueous sample